Pemidanaan Korporasi Terhadap Tindak Pidana Eksploitasi Tambang Ilegal - Ichsan, La Ode Muhammad; Saleh, La Ode Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2026)
Current developments can bring about changes in society, where crimes are no longer committed by humans but can also be committed by corporations. Corporate activities in the mining sector can cause various impacts, namely environmental damage due to mining activities. This study aims to determine corporate responsibility and the sanctions imposed due to mining activities that cause damage and losses to the community. This study is normative in nature by reviewing various literature related to this research. The results of this study are that corporate criminal responsibility is obliged to provide compensation to the community who suffers losses due to illegal mining business activities. Then, based on the theoryvicarious liabilitywhich considers vicarious liability. In addition, corporations may be subject to sanctions under Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining. The principal sanctions include imprisonment, detention, and fines. Additional sanctions include confiscation of goods used in the crime, confiscation of profits obtained from the crime, and the obligation to pay costs incurred as a result of the crime.